Springer handbook of metrology and testing - Czichos, Horst; Saito, Tetsuya; Smith, Leslie; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This Springer Handbook of Metrology and Testing presents the principles of Metrology ? the science of measurement ? and the methods and techniques of  Testing ? determining the characteristics of a given product ? as they apply to chemical and microstructural analysis, and to the measurement and testing of materials properties and performance, including modelling and simulation. The principal motivation for this Handbook stems from the increasing demands of technology for measurement results that can be used globally. Measurements within a local laboratory or manufacturing facility must be able to be reproduced accurately anywhere in the world. The Commission of the European Union has expressed this as follows: There is no science without measurements, no quality without testing, and no global markets without standards.  The Handbook is organized in five parts. Part A: Fundamentals of Metrology and Testing. Part B: Chemical and Microstructural Analysis. Part C: Materials Properties Measurement. Part D: Materials Performance Testing. Part E: Modeling and Simulation Methods.  Key Topics Metrology Principles and Organization Methodologies of Measurement and Testing Analytical Chemistry Methods Microstructural and Nanoscopic Analyses Materials Properties Measurement: mechanical, thermal, lectrical, magnetic, optical Materials Performance Testing: Corrosion, friction and wear, biogenic, environmental Nondestructive Testing Reliability Evaluation Modeling and Simulation Methods: molecular dynamics simulation, finite element methods, Monte Carlo simulation Features Develops and explains guidelines and standards for Quality of Measurement and Testing Sampling Traceability of Measurement and Testing Statistical Evaluation of Results Accuracy and Uncertainty of Measurement Validation Inter-laboratory Comparisons and Proficiency Testing Reference Materials Reference Procedures Human Aspects in a Laboratory International Standards, Laboratory Accreditation and Global Trade Chemical engineering.
Electronic reproduction.
Keywords: Metrology; Measurement; Electronic books